Clinical neuroimmunology multiple sclerosis and related disorders - Rizvi, Syed A.; Coyle, Patricia K. (Current clinical neurology., 2011)
Introduction to basic neuroimmunology and principles of immunotherapy and also serves as a thorough guide to immune-mediated disorders of the central and peripheral nervous system, as well as other systemic disorders with a significant neuroimmunologic component. The chapters are written by experts in their fields and include the most up to date scientific information. This volume is made to simplify complex immunological mechanisms and to focus on practical patient-related issues. Clinical Neuroimmunology: Multiple Sclerosis and Related Disorders is an invaluable addition to the literature and will be of significant interest to neurologists, residents and fellows, internists, and general practitioners who treat patients with neurologic disorders and other systemic autoimmune diseases.